Safety and Parental Satisfaction With Early Discharge of Preterm Infants on Nasogastric Tube Feeding and Outpatient Clinic Follow-Up - Schuler, Rahel; Ehrhardt, Harald; Mihatsch, Walter A. (Frontiers in Pediatrics, 2020)
Aim: To evaluate our early discharge program of preterm infants with nasogastric tube feeding (NTF) and close outpatient clinic follow-up with regard to safety, parent satisfaction and parental stress level.Methods: 119 preterm infants were discharged on NTF from our tertiary care neonatal unit (median gestational age 31.0 weeks, median birthweight 1650 g). Parental satisfaction was evaluated by a standardized questionnaire. For safety assessment growth until term equivalent age and rehospitalizations within two months after discharge were evaluated.Results: Infants were discharged home at a median gestational age of 35.4 weeks after a median hospital stay of 22 days. Follow up was attained in 95 of 104 parent-infant dyads. The majority of parents (94%) reported that they had made the right decision in taking their infant home on NTF. At the time of discharge 86% of parents felt very well prepared to perform NTF. 70% Of parents rated their stress level at home as low (<2 out of 5). There were no NTF associated readmissions and no growth faltering until term equivalent age.Early discharge of preterm infants with NTF together with outpatient clinic follow-up is very well accepted by parents and appears to be safe.